PENGARUSUTAMAAN GENDER DALAM PEMIKIRAN HUKUM IMÂM ABÛ HANÎFAH DAN RELEVANSINYA DENGAN PEMBAHARUAN HUKUM ISLAM - Busyro Busyro (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2016)
Imam Abu Hanifa is the founder of the Hanafi school of law which is famous for rational thought. In his periode discussion the regarding by gender haven`t known as the contemporary era, but in his ijtihads that related with women, indirectly he has given a strong position for a woman as a subject of law. This is different from the ulama mayority who often place women as objects of law. Consequences of legal thinking, among others, making women as human beings that will determine the issue of marriage, other social relations and also in matters of worship. In relation to the position of women in politics and government, Imâm Abû Hanîfah already gives the right to women to be judges in civil matters. As for the head of state, it looks like the traditions about the ban on women becoming head of state, understood the same as the scholarly opinions. Understanding it seems not prohibit absolutely, but the circumstances of women who exist in his time that causes such ijtihad. When linked with the present condition of women, presumably Imâm Abû Hanîfah will interpret the tradition in accordance with contemporary gender studies.